The Legal Rules Pertaining to Land Protection in Hungary - Fürj, Zoltán (Acta Agraria Debreceniensis, 2005)
Buildings in industry, mining, transportation and for personal and commercial activities cover increasingly more valuable agricultural land. The increase of sub-urbanization and vehicular traffic and the spread of malls and other kinds of investments are causing serious harm for not only to human society, but to a whole national economy as well.The law on agricultural land (1994:LV) contains legal rules for the preservation, use and classification of agricultural land. These rules define the temporary or permanent use of land for agricultural and non-agricultural purposes; the scale of the land-protection fee and the rules of the process on cases in which land is used for non-agricultural purposes without the consent of the land registry. In the field of land classification, the law prescribes the regulations which are to be followed in order to define the net income of agricultural land in Golden Crowns.Hungarian land protection rules are unique in the European Union, because only few member-states have similar laws to ours. Community law does not regulate the member states, except in the case of land classification, because this is the basis of the tax paid on the agricultural lands, but even here, there are differences among the states.